2022
DOI: 10.3390/diagnostics12081794
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning for Anxiety Detection Using Biosignals: A Review

Abstract: Anxiety disorder (AD) is a major mental health illness. However, due to the many symptoms and confounding factors associated with AD, it is difficult to diagnose, and patients remain untreated for a long time. Therefore, researchers have become increasingly interested in non-invasive biosignals, such as electroencephalography (EEG), electrocardiogram (ECG), electrodermal response (EDA), and respiration (RSP). Applying machine learning to these signals enables clinicians to recognize patterns of anxiety and dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Several other studies employed ECG [ 7 , 8 ] and RSP signals [ 9 , 10 ] as physiological measures for an anxiety state. Identifying biomarkers for anxiety is an essential first step to developing a machine-learning algorithm for the automatic detection of anxiety [ 11 ]. Heart-rate variability (HRV) is one of the most prominent biomarkers when using ECG signals to investigate emotions, as outlined in a recent review [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several other studies employed ECG [ 7 , 8 ] and RSP signals [ 9 , 10 ] as physiological measures for an anxiety state. Identifying biomarkers for anxiety is an essential first step to developing a machine-learning algorithm for the automatic detection of anxiety [ 11 ]. Heart-rate variability (HRV) is one of the most prominent biomarkers when using ECG signals to investigate emotions, as outlined in a recent review [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning is widely used in medical research ( Ancillon et al, 2022 ) and can assist in predicting and diagnosing psychiatric disorders by analyzing objective indicators of psychiatric disorder mechanisms ( Park et al, 2021 ). In addition, studies have shown that EEG features can achieve the best performance as classification features compared to ECG, EDA, and RSP ( Xu et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Various electrophysiological techniques, such as positron emission tomography, magnetic resonance imaging, and electroencephalography (EEG), have been widely used to measure neuronal activity [ 9 , 10 , 11 , 12 ]. Among them, EEG technology has the advantages of low cost, good portability, and strong portability [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%